Ibn Khaldun's theory of the establishment of the state, and its application to the Idrisid state - جامع, راميا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The state, according to Ibn Khaldun, is similar to a human being who is born, grows, then perishes and grows old, and annihilation is the inevitable end of every state. Every state reaches the peak of its civilization and then grows old and deteriorates until a new state comes that takes some of what the previous state left behind, restricts it and creates a different civilization, as the Idrisid state was established on a religious basis and pretension. Its founder, Idris bin Abdullah, said that his lineage goes back to the Prophet, peace and blessings be upon him, and he was able with this claim to own the lands of the Far Maghreb. He was also able, through his policy, to unite and attract the Berber tribes, so that their giving to him was without limits and came from faith, appreciation and respect, and their loyalty reached the grandson of the Messenger of God. May the peace and blessings of God be upon him, they waited for his pregnant wife until she gave birth to their child, who was Idris II. However, the Idrisid state, like any state according to Ibn Khaldun’s theory, passes through nomadism, then civilization, then perishes and collapses. Indeed, the Idrisid united the ranks of the Berbers and moved them from nomadism and the tribal stage and founded cities for them like the city of Fez. They also established an army to protect this state, but this situation did not last long, as Imam Muhammad bin Idris II and Imam Yahya divided the state among their relatives, and that was one of the first signs of weakness. Then they created loyalists and followers from among the non-Berbers, and the compliance of some The Idrisid princes’ whims and changing their loyalty from time to time were among the factors that played a major role in the collapse of their state and its fall at the hands of the Umayyads of Andalusia.